Development and validation of the patient reported outcomes questionnaire of children with asthma in China: A Caregiver's proxy-reported measure - Xu, Tong; Zhang, Haiyue; Zhang, Yuhai; Yang, Peng; Yang, Zhe; Jiang, Xun; Shang, Lei (Frontiers in Pediatrics, 2023)
Background: Research on asthma control levels and quality of life is important for children with asthma during their growth stage. Therefore, it is necessary to develop a questionnaire that can be used for monitoring and evaluating the disease control effectiveness and quality of life of children with asthma in China and to conduct a preliminary evaluation for its reliability, validity, and discriminative ability. Methods: The questionnaire was created through a literature review and qualitative interviews for a targeted population. Based on the previous work, a collection of items was reviewed and discussed by 30 caregivers of children with asthma and 5 experienced pediatricians, and then 72 items were screened and selected to form the draft questionnaire. After three rounds of investigation (with 240, 503, and 360 participants respectively), the final questionnaire was established according to the evaluation results. The structure of the questionnaire was explored through confirmatory factor analysis. Exploratory factor analysis and variability analysis were applied based on first two rounds of investigation. Reliability, construct validity, and discriminative ability were evaluated based on the third round of investigation. Results: The questionnaire contains 6 dimensions and 34 items, and the total cumulative variance contribution rate was 54.96%; Cronbach’s α coefficient was 0.91; the split-half reliability coefficient was 0.75, and the test-retest reliability coefficient was 0.74. The children’s age, gender, residence, asthma attack in last three months, caregivers’ education background, and monthly income per caregiver were correlated with patient-reported outcomes of children with asthma. Conclusion: The questionnaire appeared to have good reliability, construct validity, and discriminative ability in children with asthma in China.